An RGB Multi-Channel Representation for Images on Quantum Computers - Sun, Bo; Iliyasu, Abdullah M.; Yan, Fei; Dong, Fangyan; Hirota, Kaoru (Journal of advanced computational intelligence and intelligent informatics, 2013)
RGB multi channel representation is proposed for images on quantum computers (MCQI) that captures information about colors (RGB channels) and their corresponding positions in an image in a normalized quantum state. The proposed representation makes it possible to store the RGB information about an image simultaneously by using 2 n +3 qubits for encoding 2 n × 2 n pixel images, whereas pixel-wise processing is necessary in many other quantum image representations, e.g., qubit lattice, grid qubit, and quantum lattice. Simulation of storage and retrieval of MCQI images using human facial images demonstrated that 15 qubits are required for encoding 64 × 64 colored images, and encoded information is retrieved by measurement. Perspectives of designing quantum image operators are also discussed based onMCQI representation, e.g., channel of interest, channel swapping, and restrict version of color transformation.